Exposure to crocidolite and the incidence of different histological types of lung cancer. - de Klerk, N H (1996)
OBJECTIVES: To estimate the relations between exposure to both tobacco smoke and crocidolite and the incidence of various histological types of lung cancer. METHODS: In 1979 all former workers from the Wittenoom asbestos industry who could be traced were sent a questionnaire on smoking history. Of 2928 questionnaires sent, satisfactory replies were received from 2400 men and 149 women. Of the men, 80% had smoked at some time and 50% still smoked. Occupational exposure to crocidolite was known from employment records and follow up was maintained through death and cancer registries in Australia with histological diagnoses obtained from the relevant State Cancer Registry. Conditional logistic regression was used to estimate the effects of tobacco and asbestos exposure on incidence of different cell types of lung cancer in a nested case-control design. RESULTS: Between 1979 and 1990, 71 cases of lung cancer occurred among men in this cohort: 27% squamous cell carcinoma, 31% adenocarcinoma, 18% small cell carcinoma, 11% large cell carcinoma, and 13% unclassified or indeterminate. Two of the classified cases and one unclassified case had never smoked. The incidence of both squamous and adenocarcinoma types of lung cancer were greatest in ex-smokers and in those subjects with the highest levels of exposure to crocidolite. After adjustment for smoking habit, the increase in incidence of lung cancer with increasing exposure to crocidolite was greater for squamous cell carcinoma than for adenocarcinoma. CONCLUSIONS: The results from this study have shown significant exposure-response effects for exposure to crocidolite, and both adenocarcinoma and squamous cell carcinoma of the lung. They also provide some further evidence against the theory that parenchymal fibrosis induced by asbestos is a necessary precursor to asbestos induced lung cancer.